Co-Adjuvant Nanoparticles for Radiotherapy Treatments of Oncological Diseases - Roberta Crapanzano; Valeria Secchi; Irene Villa (Applied Sciences, 2021)
Nanomedicine is emerging as promising approach for the implementation of oncological methods. In this review, we describe the most recent methods exploiting heavy nanoparticles and hybrid nanomaterials aiming at improving the traditional X-rays-based treatments. High-Z nanoparticles are proposed as radiosensitizers due to their ability to stop the ionizing radiation and to increase the locally delivered therapeutic dose. Other nanoparticles working as catalysts can generate reactive oxygen species upon X-rays exposure. Thanks to their high toxicity and reactivity, these species promote DNA cancer cells damage and apoptosis. Hybrid nanoparticles, composed by scintillators coupled to organic molecules, are suitable in X-rays activated photodynamic therapy. This work highlights the roles played by the diverse nanoparticles, upon ionizing radiation irradiation, according to their physico-chemical properties, surface functionalization, and targeting strategies. The description of nanoparticle qualities demanded by the oncological nanomedicine is presented in relation to the processes occurring in biological medium when X-ray radiation interacts with heavy nanoparticles, including the scintillation mechanisms, the stopping power amplification, and the disputed modeling of the effective deposit of energy within nanomaterials. The comprehension of these issues in nanomedicine drives the strategies of nanoparticles engineering and paves the way for the development of advanced medical therapies.